Peranan Penyuluh Dalam Penerapan Paket Teknologi Pada Usaha Peternakan Kerbau (Studi Kasus Pada Kelompok Ternak "Kabau Antrada" Kecamatan Koto Baru Kabupaten Dharmasraya) - Ediset Ediset; A. Anas (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2013)
The research was conducted to know technology-application level and elucidator part on “Kabau Antrada” group in Dhamasraya. Research method use was  case study method with census taken sample, which mean all of the 21 person members kabau antrada group became respondent.. Observation and interviewed (questioners) was done to get primary data. The result shown that every topic has given increased the technology-application at kabau antrada group Koto Baru District Dhamasraya Regency. For example selection of breeding stock increased 76.19%, feed increased 73.47%, management improvement increases 74.83%, diseases prevention increased 71.43%,  followed product selling 73.21%. The average of “panca usaha ternak” was 73.83%. Extension part not so deep on “kabau antrada” group even thought the average technology-packet on panca usaha tani has increased. These increasing caused of farmer experience and academicians part.